The Effects of Water Content Variation on Adhesion Factor of Pile Foundation in Expansive Soil - Tjandra, D.; Indarto, .; Soemitro, R.A.A. (Civil Engineering Dimension, 2013)
Seasonal change causes variations in soil moisture content. On expansive soil, this condition influences soil moisture content in the active zone, which is approximately in five meters depth. The water content variation induces the changes in soil characteristics and these changes have an impact to adhesion factor of piles. The main objective of this research is to investigate the influence of water content variations on adhesion factor of piles. A series of laboratory experiments were conducted considering water content variations. A pile model made of concrete was penetrated to soil sample which was placed in a cylindrical tube of diameter about 15 times the diameter of the pile model. The pile model was loaded until failure to investigate the friction capacity. The results showed that the change of water content have great impact to adhesion factor of piles and its friction capacity decreased up to eight times from drying to wetting condition.